Red and processed meat consumption and risk of glioma in adults: A systematic review and meta-analysis of observational studies - Parvane Saneei; Walter Willett; Ahmad Esmaillzadeh (Journal of Research in Medical Sciences, 2015)
Background: These findings from several observational studies, investigated the association between red meat consumption and gliomas, were inconsistent. We conducted a systematic review and meta-analysis of observational studies to summarize available date on the relation between meat intake and risk of glioma. Materials and Methods: A systematic literature search of relevant reports published until May 2014 of the PubMed/Medline, ISI Web of Knowledge, Excerpta Medica database, Ovid database, Google Scholar, and Scopus databases was conducted. From 723 articles yielded in the preliminary literature search, data from eighteen publications (14 case-control, three cohort, and one nested case-control study) on unprocessed red meat, processed meat, and/or total red meat consumption in relation to glioma in adults were included in the analysis. Quality assessment of studies was performed. Random effects model was used to conduct the meta-analysis. Results: We found a positive significant association between unprocessed red meat intake and risk of glioma (relative risk [RR] = 1.30; 95% confidence interval [CI]: 1.08-1.58) after excluding three studies with uncertain type of brain cancer. This analysis included only one cohort study which revealed no relation between unprocessed red meat intake and glioma (RR = 1.75; 95% CI: 0.35-8.77). Consumption of processed meats was not related to increased risk of glioma in population-based case-control studies (RR = 1.26; 95% CI: 1.05-1.51) and reduced risk in hospital-based case-controls (RR = 0.79; 95% CI: 0.65-0.97). No significant association was seen between processed red meat intake and risk of glioma in cohort studies (RR: 1.08; 95% CI: 0.84-1.37). Total red meat consumption was not associated with risk of adult glioma in case-control or cohort studies. Conclusion: In this meta-analysis of 18 observational studies, we found a modest positive association between unprocessed red meat intake and risk of gliomas based almost entirely on case-control studies. Processed red meat was overall not associated with risk of gliomas in case-control or cohort studies.